Chemical Composition of Lantana camara Fruit Essential Oil - Kumar Singh, Rabindra; Tiwari, Balendra; Sharma, Uma; Prasad Singh, Satyendra (Asian Journal of Chemistry, 2012)
Lantana camara fruit essential oil was extracted by hydro distillation and compositional analysis carried out by GC and GCMS. It identified 37 constituents representing 74.31 % oil, of which components were trans-b-caryophyllene (21.42), sabinene (1.13 %), eucalyptol (1.25 %), a-humulene (9.97 %), bicyclogermacrene (2.18 %), germacrene D (2.19 %) and trans-nerolidol (18.85 %).